Management and Potential for Developing Wakaf Productivity - Surati, Surati; Fikriawan, Suad; Nafi'ah, Nafi'ah (Indonesian Journal of Islamic Economics and Finance, 2022)
The purpose of this research is to know about how to manage and develop land waqf in Cokromenggalan Ponorogo Village, and about the potential for developing waqf productivity in Cokromenggalan Ponorogo Village. The research method used in this study is a qualitative method using an inductive approach, the data collection techniques used are observation, interview and documentations. The results of this study are the management and development of waqf in Cokromenggalan Village managed by nadzir with the assistance of the local mosque administrator (ta'mir). In the distribution of waqf assets, the majority are in the form of mosques, prayer rooms, and educational institutions. As for the potential development of waqf productivity, it is still not maximized, due to limited human resources, costs, and public awareness to manage waqf is still lacking.